2018
DOI: 10.1177/0361198118794534
|View full text |Cite
|
Sign up to set email alerts
|

Improving High-Frequency Transit Performance through Headway-Based Dispatching: Development and Implementation of a Real-Time Decision-Support System on a Multi-Branch Light Rail Line

Abstract: Service reliability is a major concern for public transportation agencies. Transit services experience natural variability in operations performance, due to factors such as congestion, changes in demand, and operator behavior. This variability leads to irregular headways, resulting in longer passenger waits and decreased effective capacity as gaps in service form. Real-time control strategies allow controllers to regulate service and improve performance. This research tested the effectiveness of a headway-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…They concluded that technical failures and operator compliance were persistent challenges. Tablets were also used by terminal personnel in a light-rail, multi-branch line in Boston to support an even-headway policy in their dispatching strategy ( 8 ). Berrebi et al ( 9 ) reported small-scale implementations of headway control on the Atlanta streetcar system and a bus route in San Antonio.…”
Section: Headway Control: the Premise The Promise And Potential Pitfallsmentioning
confidence: 99%
“…They concluded that technical failures and operator compliance were persistent challenges. Tablets were also used by terminal personnel in a light-rail, multi-branch line in Boston to support an even-headway policy in their dispatching strategy ( 8 ). Berrebi et al ( 9 ) reported small-scale implementations of headway control on the Atlanta streetcar system and a bus route in San Antonio.…”
Section: Headway Control: the Premise The Promise And Potential Pitfallsmentioning
confidence: 99%